INTESTINAL DYSBIOSIS: A Nutritional Approach (REMUNOM, 2024)
The intestinal microbiota is composed of a vast population of living microorganisms that inhabit the intestine, performing essential functions such as preventing the invasion of pathogenic agents. Intestinal dysbiosis, a disorder in this microbial balance, compromises the integrity of the intestinal mucosa and promotes the predominance of harmful bacteria. Adequate nutrition is fundamental for intestinal health, aiding in the recovery and maintenance of intestinal integrity. Given this, the present article aims to highlight the role of nutrition in the treatment of intestinal dysbiosis, emphasizing its importance as an ally in intestinal health. To this end, it is crucial to address intestinal dysbiosis and list the components used in the nutritional treatment of patients with intestinal dysbiosis. The justification for choosing this theme lies in the increasing prevalence of intestinal disorders, such as irritable bowel syndrome, inflammatory bowel disease, and food intolerances, which significantly affect the quality of life of millions of people worldwide. Regarding the applied methodology, this study is a qualitative research, presenting descriptive research as the approach method. The research technique adopted for the study's foundation is limited to a literature review. In the end, it was possible to note that probiotics, prebiotics, symbiotics, and glutamine have proven to be effective strategies in the treatment of intestinal dysbiosis.